Distribution of urokinase-type plasminogen activator immunoreactivity in the mouse (The Rockefeller University Press, 1984)
Immunocytochemistry, using rabbit antibodies to a urokinase-type 48- Kdalton Mr mouse plasminogen activator, showed that enzyme immunoreactivity is widely distributed in the normal mouse. Strong staining was obtained in widely disseminated connective tissue cells with a fibroblast-like morphology. Such cells occurred in high numbers in the lamina propria mucosae of the gastrointestinal tract, and in moderate numbers in the connective tissue septa of the pancreas. A few such cells were detected around the larynx, trachea, and bronchi. Immunoreactivity also occurred in epithelial cells of the proximal and distal kidney tubules, the ductus deferens, and in pulmonary pneumocytes. In addition, presumably extracellular staining was seen irregularly along the basement membrane and fibrillar structures in the lamina propria of the small and large intestines. Moreover, decidual cells of the mouse placenta stained strongly, and a moderate staining was observed in epithelial cells of involuting mammary glands, but not in those of noninvoluting glands. No immunoreactivity was observed in endothelial cells. Control experiments included absorption of the antibodies against highly-purified mouse plasminogen activator and the corresponding proenzyme, and the finding of a good correspondence between the number of immunoreactive cells and measurable enzymatic activity determined in adjacent tissue sections. Separation by SDS PAGE followed by immunoblotting revealed only one immunochemically stainable protein band with Mr approximately 48 Kdaltons in extracts from tissues showing immunoreactivity.